Influence of the planting season, insecticides and plant population on insect damage and yield of upland rice - Ferreira, Evane; Czepak, Cecília (Pesquisa Agropecuaria Brasileira, 1997)
The influence of four planting dates (Oct. 20, 1987; Nov. 17, 1987; Dec. 21, 1987 and Jan. 14, 1988), three seeding rates (32, 54 and 75 seeds/m) and five insecticides (carbofuran 50 G, furathiocarb 666 TS, carbofuran 350 TS, thiodicarb 350 TS e deltamethrin 25 CE) was evaluated on insect damage and grain yield of the upland rice cultivar IAC-47. In overall, the percentage of dead culms caused by Deois flavopicta, Elasmopalpus lignosellus and underground termites ranged from 5.4% to 24.3% and grain production was between 500 and 2,317 kg/ha. Planting in November appeared to be the most efficient procedure to reduce insect damage and attain maximum grain yield. Gain obtained from insecticide applications was greater when rice was planted in October, but it was considerably reduced in November. Association between carbofuran 50 G and the highest seeding rate was very important in reducing D. flavopicta populations for the earliest planting season.
Keywords: Oryza sativa; grass spittlebug; stem borer; underground termites; pest management; chemical control; crop management